Divergent socioeconomic drivers of land use at various times in the Hulunber grassland area, China - Zhu Xiaoyu (Elsevier, 2021)
The effects of socioeconomic changes on land use dynamics have been increasingly investigated around the world, but our knowledge of the processes underlying these effects over decades needs more attention for sustainable land management. In this research, structural equation modelling (SEM) was used to analyse the relationships among the regional economy, livestock factors and land use. We found that the land use changes were not consistent from 1990 to 2015, which was attributed to different driving forces. In the last decade of the 20th century, land use changes mainly featured the expansion of croplands at the expense of grasslands. In the 21st century, forestlands and grasslands increased due to the implementation of the Grain for Green Programme, and building lands increased because of urbanization and economic development. Our SEM results demonstrated that livestock was the major driving force of land use changes in 1990–2019, while the regional economy mainly drove land use changes in 2000–2009 in the Hulunber grassland area. Further, the added values of secondary and tertiary industries had a greater effect than the added value of primary industry and the urban population in 1990–2019; in contrast, the urban population rather than the added values of primary and tertiary industries better represented the changes in the regional economy. Meanwhile, the number of small livestock had a stronger influence than the number of large livestock and the rural population in 1990–2019, while the opposite situation was observed in a specific period (2000–2009). The socioeconomic driving factors of land use changes are divergent and dynamic over time, and regional-scale and local particularities should be brought to the forefront of land resource planning.